THE EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF HOTEL EMPLOYEES, MURIA SEMARANG - Arta Adi Kusuma (SEAN Institute, 2021)
The population in this study were all 115 employees of Hotel Muria Semarang. The sample was determined by proportional random sampling technique, with 53 respondents as respondents. The data collection method used is a questionnaire (questionnaire) and documentation method. The data analysis method used in this research is the percentage description analysis method and multiple linear regression. Based on the results of the study, it was obtained that the multiple linear regression equation = 23.857 + 0.180 X1 + 0.94 X2. By using SPSS 16 the results of the F test hypothesis show F count = 16,646 with a significance value = 0.000 <0.05 which means H3 which reads